A novel circular RNA circNLRP3 alleviated ricin toxin-induced TNF-α production through sponging miR-221–5p. (1st March 2023) - Chen, Wei; Chang, Ying; Sun, Chengbiao; Xu, Meng; Dong, Mingxin; Zhao, Na; Wang, Yan; Zhang, Jianxu; Xu, Na; Liu, Wensen
Abstract: Acting as microRNA (miRNA) sponges, circular RNAs (circRNAs) have been discovered to be critical modulators of inflammatory processes. Ricin Toxin (RT) is highly toxic to mammalian cells and low doses of RT can induce acute inflammation. However, current researches on the underlying mechanism and function of circRNA/miRNA network in RT-induced inflammation are limited. Previously, we found miR-221–5p was aberrant and associated with the inflammation of RT induction. In this study, based on the circRNA high-throughput sequencing (circRNA-seq), we obtained a novel circRNA termed circNLRP3 and revealed that circNLRP3 can sponge miR-221–5p, release its target mRNA A20, and further suppress NF-κB signaling pathway to alleviated RT-induced TNF-α production. Our findings elucidated a possible mechanistic link between the circNLRP3/miR-221–5p/A20 axis and RT-induced inflammatory response, which may broaden our understanding of RT poisoning. Graphical abstract: Image 1 Highlights: A novel circRNA circNLRP3 is obtained in RAW264.7 cells. The miR-221–5p/A20/NF-κB axis is involved in the ricin toxin-induced pro-inflammation cytokine TNF-α production of RAW264.7 cells. CircNLRP3 as a miR-221–5p sponge plays a negative role in the ricin toxin-induced TNF-α secretion via A20/NF-κB pathway.